Design of head-driven phrase structure grammar for Bangla - Ayesha Binte Mosaddeque; Ali, M. Hammad; Haque, Nafid (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2006.